Edukasi Cegah Penyakit Tidak Menular Dengan Perilaku CERDIK Di SMAN 11 Kota Jambi - Marta Butar Butar; M.Dody Izhar; Rizalia Wardiah (Jurnal Salam Sehat Masyarakat (JSSM), 2022)
Cerdik behavior is a behavior that is needed to prevent various kinds of non-communicable diseases. The behavior in question is regular health checks, getting rid of cigarette smoke, diligent physical activity/sports, and a healthy and balanced diet. With the increase in knowledge related to these matters, it is hoped that it can increase awareness for the smart lifestyle in the lives of participating students at SMAN 11 Jambi City. Community service is carried out through socialization in the form of counseling on efforts to prevent non-communicable diseases with smart behavior and discussion activities for cadres to prevent non-communicable diseases with smart behavior. The results of the socialization activities to prevent non-communicable diseases with Cerdik Behavior showed that there was an increase in the knowledge of participants who participated in the activity when compared to before and after participating in the training, from 72,25 to 76,75. Statistical results (Wilcoxon Test) obtained p value = 0.019, meaning that there is a significant difference in the average test scores before being given counseling and after being given counseling. It is hoped that there will be the formation of Cadre of CerdikBehavior at SMAN 11 Jambi City and the provision of interesting pocket books by students.